2007
DOI: 10.1063/1.2789417
|View full text |Cite
|
Sign up to set email alerts
|

Efficient stochastic simulations of complex reaction networks on surfaces

Abstract: Surfaces serve as highly efficient catalysts for a vast variety of chemical reactions. Typically, such surface reactions involve billions of molecules which diffuse and react over macroscopic areas.Therefore, stochastic fluctuations are negligible and the reaction rates can be evaluated using rate equations, which are based on the mean-field approximation. However, in case that the surface is partitioned into a large number of disconnected microscopic domains, the number of reactants in each domain becomes sma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 67 publications
0
42
0
Order By: Relevance
“…The network that involves H, O, and CO molecules, from which ice mantles containing H 2 O, CO 2 and CH 3 OH are formed by successive hydrogenation and oxydation reactions, is promising (Barzel & Biham 2007b). Unlike the H and D atoms, these heavier atoms and molecules are more strongly bound to both the surface and each other and do not exhibit the Langmuir rejection property.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The network that involves H, O, and CO molecules, from which ice mantles containing H 2 O, CO 2 and CH 3 OH are formed by successive hydrogenation and oxydation reactions, is promising (Barzel & Biham 2007b). Unlike the H and D atoms, these heavier atoms and molecules are more strongly bound to both the surface and each other and do not exhibit the Langmuir rejection property.…”
Section: Discussionmentioning
confidence: 99%
“…We apply the same technique as in Barzel & Biham (2007b) to derive the corresponding moment equations when the additional terms introduced by the Langmuir rejection are included. The time derivatives of the moments introduced by the term proportional to f I are…”
Section: Moment Equationsmentioning
confidence: 99%
“…In spite of its good accuracy for grain surfaces, this method can only be used for small chemical networks since the number of equations grows exponentially with the number of species. Lipshtat & Biham (2003) have thus introduced another method based on the time derivatives of the moments to study the formation of molecular hydrogen, while Barzel & Biham (2007) have extended this method for more complex chemical networks. The comparisons between the methods introduced here show that the rate equations method tends to overestimate the reaction rates and the abundance of the reactants, especially when they are in low quantities.…”
Section: The Computational Methodsmentioning
confidence: 99%
“…Moreover, in practice one can obtain accurate results using surprisingly low values of the cutoffs. In fact, in an earlier version of this formulation, it was shown that for a broad range of conditions the cutoff C = 2 is sufficient [13,14]. In this case, the equations include first order moments that account for the average population sizes and second order moments that account for the number of pairs of species X i and X j in the system, from which the reaction rates are evaluated.…”
mentioning
confidence: 99%
“…The difficulty with moment equations is that higher order moments appear on the right hand side of each equation. To obtain a closed set of equations one needs to apply a suitable truncation scheme, in which the higher order moments are expressed in terms of low order moments [11][12][13][14]. In practice, the truncation is typically done at the level of third order moments, namely only the first and second order moments are taken into account.…”
mentioning
confidence: 99%